Comprehensive Analysis Revealed the Potential Implications of m6A Regulators in Lung Adenocarcinoma - Xie, Lingling; Dai, Rongyang; Wang, Xudong; Xie, Guangfei; Gao, Zhihua; Xu, Xinxin (Frontiers in Molecular Biosciences, 2022)
Abstract Background: The biological signification of RNA N6-methyladenosine (m6A) decoration in tumorigenicity and progression has been highlighted in recent studies, but whether m6A modification plays a potential role in tumor microenvironment (TME) formation and immune regulation in lung adenocarcinoma (LUAD) remains unclear. Methods: m6A modification features were evaluated by analyzing the multi-omics features of 17 m6A regulators in over 1900 LUAD samples, and at the same time the correlation between these modification patterns and TME characteristics was analyzed. A m6A score signature-based principal components analysis (PCA) algorithm was constructed to assess the prognosis and responses of individual patients to immunotherapeutic and targeted therapies. Results: Three different m6A modification patterns were determined in 1901 LUAD samples, which were found to be related to diverse clinical outcomes via different biological pathways. Based on the m6A score extracted from the m6A-associated signature genes, LUAD patients were separated into high- and low-m6Ascore groups. It was discovered that patients with high m6A scores had longer survival, lower tumor mutation loads and low PD-L1 / PDCD1 / CTLA4 / TAG3 expression level. In addition, LUAD patients with high m6A scores displayed lower IC50 to some targeted drugs including Nilotinib, Erlotinib, Imatinib and Lapatinib. Conclusions: m6A modification was significantly associated with TME and clinical outcomes. These findings may help gain more insights into the role of m6A decoration in the molecular mechanism of LUAD, thus facilitating the development of more effective personalized treatment strategies.